1999
DOI: 10.1093/jnci/91.6.523
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Response in Solid Tumors: Unidimensional Versus Bidimensional Measurement

Abstract: Background: Tumor shrinkage is a common end point used in screening new cytotoxic agents. The standard World Health Organization criterion for partial response is a 50% or more decrease in the sum of the products of two measurements (the maximum diameter of a tumor and the largest diameter perpendicular to this maximum diameter) of individual tumors. However, theoretically, the simple sum of the maximum diameters of individual tumors is more linearly related to cell kill than is the sum of the bidimensional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
204
1
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 373 publications
(226 citation statements)
references
References 6 publications
7
204
1
7
Order By: Relevance
“…Actually, the response evaluation with RECIST is extremely simple and we could not show any significant differences between the evaluation results (overall response rate and survival) with the WHO criteria and those with RECIST, in measurable lesions of 20 mm or more. This should clearly indicate the validity of the RECIST and the uselessness of two-dimensional measurements, as pointed out by James et al [8].…”
Section: Discussionmentioning
confidence: 53%
“…Actually, the response evaluation with RECIST is extremely simple and we could not show any significant differences between the evaluation results (overall response rate and survival) with the WHO criteria and those with RECIST, in measurable lesions of 20 mm or more. This should clearly indicate the validity of the RECIST and the uselessness of two-dimensional measurements, as pointed out by James et al [8].…”
Section: Discussionmentioning
confidence: 53%
“…Although three-dimensional volume measurements have been advocated as reliable methods particularly for the evaluation of solid nodules, until now, there have been few data supporting the use of this approach for GGO nodules. In general, the one dimensional measurement of tumor maximum diameter has been considered sufficient for assessing changes in tumor volume and ascertaining reproducibility especially for solid tumors [8]. Moreover, according to RECIST introduced in 2000 [9], tumor size measurements are conducted by the use of uni-dimensional method.…”
Section: Discussionmentioning
confidence: 99%
“…More information on this population and historical records can be found in Gomez-Raya et al (2009). In this study, length was used as a criterion for estimating tumor size based on James et al (1999), who concluded that unidimensional measurements for tumors are appropriate for estimating regression in solid tumors. Pigs whose tumors had reached the maximum length at collection time were considered as progressing animals.…”
Section: Gene Expression During Tumor Progression and Regressionmentioning
confidence: 99%